Innate Immunity against Leishmania Infections - Gurung, Prajwal (Cell Microbiol, 2015)
Leishmaniasis is a major health problem that affects more than 300 million people throughout the world. The morbidity associated with the disease causes serious economic burden in Leishmania endemic regions. Despite the morbidity and economic burden associated with Leishmaniasis, this disease rarely gets noticed and is still categorized under neglected tropical diseases. The lack of research combined with the ability of Leishmania to evade immune recognition has rendered our efforts to design therapeutic treatments or vaccines challenging. Herein, we review the literature on Leishmania from innate immune perspective and discuss potential problems as well as solutions and future directions that could aid in identifying novel therapeutic targets to eliminate this parasite.